An open‐label phase 2 trial of entospletinib in indolent non‐Hodgkin lymphoma and mantle cell lymphoma. (5th September 2018) - Andorsky, David J.; Kolibaba, Kathryn S.; Assouline, Sarit; Forero‐Torres, Andres; Jones, Vicky; Klein, Leonard M.; Patel‐Donnelly, Dipti; Smith, Mitchell; Ye, Wei; Shi, Wen; Yasenchak, Christopher A.; Sharman, Jeff P.
Summary: Spleen tyrosine kinase (Syk) mediates B‐cell receptor signalling in normal and malignant B cells. Entospletinib is an oral, selective Syk inhibitor. Entospletinib monotherapy was evaluated in a multicentre, phase 2 study of patients with relapsed or refractory indolent non‐Hodgkin lymphoma or mantle cell lymphoma (MCL). Subjects received 800 mg entospletinib twice daily. Forty‐one follicular lymphoma (FL), 17 lymphoplasmacytoid lymphoma/Waldenström macroglobulinaemia (LPL/WM), 17 marginal zone lymphoma (MZL) and 39 MCL patients were evaluated. The primary endpoint was a progression‐free survival (PFS) rate (defined as not experiencing progression or death) at 16 weeks for patients with MCL and at 24 weeks for patients with FL, LPL/WM and MZL. The most common treatment‐emergent adverse events were fatigue, nausea, diarrhoea, vomiting, headache and cough. Common laboratory abnormalities were anaemia, neutropenia and thrombocytopenia; aspartate transaminase, alanine transaminase, total bilirubin and serum creatinine were all increased. PFS at 16 weeks in the MCL cohort was 63·9% [95% confidence interval (CI) 45–77·8%]; PFS at 24 weeks in the FL, LPL/WM, MCL and MZL cohorts was 51·5% (95% CI 32·8–67·4%), 69·8% (95% CI 31·8–89·4%), 56·6% (95% CI 37·5–71·8%) and 46·2% (95% CI 18·5–70·2%), respectively. Entospletinib had limited single‐agent activity with manageable toxicity in these patient populations.